English Teacher Identity in EFL Higher Education: Exploring Perspective from Critical Reflection - Andriani, Agis; Izzati, Aina Amalia (English Teaching and Linguistics Journal (ETLiJ), 2025)
Teacher identity has a significant impact on teachers’ decisions on teaching processes, teaching and learning material, teacher-student relationships, and professional development. However, in its implementation, there is unclear identity that confuses the standards, and a lack of charisma in the EFL teacher profile, while an ideal language teacher is crucial to building a successful learning to foreign language. Data taken from critical reflection (Rolfe, 2014) written by English education department students. They are university students who joins English Phonetics and Phonology class. The tutor facilitates the teaching learning based on the principal of critical language awareness. Data are analyzed based on the foundation the framework Van Dijk identity construction (van Dijk, 2015). There result shows that identity represented to what someone thinking, belief, and perceive, and it realizes into social practice (teaching and learning English as foreign language). In this context, it creates the teacher or lecturer to be the agent of change. For the research, interview should be conducted to explore deeper understanding how the teacher construct EFL identity to support the success of EFL teaching learning process.